Elimination and Substitution, Algebra

5x - y = 1
-15x +4y = 6
Posted Date: 3/10/2013 6:19:46 PM | Location :







Related Discussions:- Elimination and Substitution, Assignment Help, Ask Question on Elimination and Substitution, Get Answer, Expert's Help, Elimination and Substitution Discussions

Write discussion on Elimination and Substitution
Your posts are moderated
Related Questions

25 equations that equall 36


if log a-b/2=1/2 (log a + log b) show that a*a+b*b=6ab

what the hell is the problem to this solution .

Qs1=-7+P1 (2) Qd1=15-P1+2P2+P3 (3) Qs1=Qd1

In previous section we looked at the two functions  f ( x) = 3x - 2 and g ( x )= x/3 + 2/3 and saw that                                          ( f o g ) ( x ) =(g o f )( x ) =

how would you divide a negative fraction with a positve fraction

Logarithm form In this definition y = log b  x is called the logarithm form Exponential form In this definition b y = x is called the exponential form.